Soft Drink Consumption Patterns of Middle School Students in North Okkalarpa - Thwe, Moh Moh; May, Sein Yaw; Aung, Min Htike (Makara Journal of Health Research, 2021)
Background: Urbanization and economic development in Myanmar have brought about culture and dietary transition from a traditional to a westernized diet. The health of the nation, especially the youth, may influence the changing dietary patterns: i.e., the higher the soft drink consumption, the higher the prevalence of soft drink-related diseases. Methods: This cross-sectional study was carried out among 250 middle school students in North Okkalarpa Township, Yangon Region. Data were collected using self-structured questionnaires, and respondents were selected by using simple random sampling method. Results: In this study, 81.2% of the students consumed soft drink once a day, and the main reasons were taste, preference, and availability at home. Chi-square test showed significant relationship between gender and soft drink consumption patterns (p = 0.005), and a strong significant relationship was observed between education level and soft drink consumption patterns (p = 0.000). However, Kruskal–Wallis statistics showed significant relationship between education level and soft drink consumption habit (p = 0.003). Conclusions: This study focused on the knowledge regarding soft drink, habits, and consumption patterns among students. This study highlighted that knowledge of preventive measures of non-communicable diseases since school age can also reduce the disease burden of Myanmar.